Study protocol for a quasi-experimental claims-based study evaluating 10-year results of the population-based integrated healthcare model 'Gesundes Kinzigtal' (Healthy Kinzigtal): the INTEGRAL study. Issue 1 (15th January 2019) - Schubert, Ingrid; Siegel, Achim; Graf, Erika; Farin-Glattacker, Erik; Ihle, Peter; Köster, Ingrid; Stelzer, Dominikus; Mehl, Claudia; Schmitz, Jutta; Dröge, Patrik; Günster, Christian; Klöss, Andreas; et al.
Abstract : Introduction: Patients often experience interface problems when treated by different specialists and in different healthcare sectors. Integrated care concepts aim to reduce these problems. While most integrated healthcare models focus on individual diseases, the integrated care model 'Gesundes Kinzigtal' applies a population-based approach and addresses the full spectrum of morbidities for a population defined by area of residence—the Kinzigtal. A special feature of the model is the joint savings contract between the regional management company and the statutory health insurers. The INTEGRAL study aims at assessing the effectiveness of 'Gesundes Kinzigtal' under routine conditions in comparison to conventional care over a period of 10 years in order to understand the benefits but also the potential for (unintended) harms. Methods and analysis: Database Claims data from statutory health insurance funds 2005–2015. The evaluation consists of a quasi-experimental study, with Kinzigtal as intervention region, at least 10 further regions with a similar population and healthcare infrastructure as primary controls and an additional random sample of insurees from the federal state of Baden-Württemberg as secondary controls. Model-specific and 'non-specific' indicators adopted from the literature and enriched by focus group interviews will be used to evaluate the model's effectiveness and potential unintended consequences by analysing healthcare utilisation in general. Temporal trends per indicator in the intervention region will be compared with those in each control region. The overall variation in trends for the indicators across all regions provides information about the potential to modify an indicator due to local differences in the healthcare system. Ethics and dissemination: Ethic Commission of the Faculty of Medicine, Philipps-University Marburg (ek_mr_geraedts_131117). Results will be discussed in workshops, submitted for publication in peer-review journals and presented at conferences. Trial registration number: DRKS00012804.